TREN KAJIAN AL-QURâAN DI DUNIA BARAT - Rahman, Yusuf (Jurnal Studia Insania, 2013)
This research was partially take reference by Edward Said in his Orientalism in 1978 have criticized the Orientalists which he said was biased against Western thought and culture, Orientalist studies of the Al-Qurâan, we could divide them into two general categories, the first group âoldâ Orientalism (Orientalism âThe Pastâ). This paradigm shift occurred from philological approach, criticism of the text of the Al-Qurâan to approach literature; study the Al-Qurâan in the Western world in recent years is very widespread and growing. In contrast to previous studies in the past were very much influenced by the spirit of colonialism, and orientalism misionarisme, study the Al-Qurâan in recent years shows an understanding and appreciation of intellectual property